2020
DOI: 10.1186/s12933-020-00996-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of cardiovascular mortality by strict glycemic control (pre-procedural HbA1c < 6.5%) in Japanese medically-treated diabetic patients following percutaneous coronary intervention: a 10-year follow-up study

Abstract: Background: In the secondary prevention of cardiovascular (CV) disease in patients with diabetes, an optimal level of HbA1c, the most widely-used glycemic control indicator, for favorable clinical consequences still remains to be established. This study assessed the association between preprocedural HbA1c level and CV mortality in Japanese diabetic patients undergoing percutaneous coronary intervention (PCI). Methods: This is a retrospective observational study using a single-center prospective PCI database in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…A recent study in a smaller study population from Spain could also show the additional benefit of including HbA 1c levels for the association with CVD [ 1 ]. Extending the importance of HbA 1c levels in the clinical practice, additional data pointing out the usage of HbA 1c levels for risk stratification in patients with CVD or DM with an insufficient glucose control in patients from Asia should be noted [ 13 , 14 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in a smaller study population from Spain could also show the additional benefit of including HbA 1c levels for the association with CVD [ 1 ]. Extending the importance of HbA 1c levels in the clinical practice, additional data pointing out the usage of HbA 1c levels for risk stratification in patients with CVD or DM with an insufficient glucose control in patients from Asia should be noted [ 13 , 14 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor glycemic control was associated with an increased risk of mortality (HbA1c > 10%) [ 17 ] and CV events (HbA1c > 7%) [ 18 ]. A study reported that stringent glycemic control (HbA1c < 6.5%) was associated with the risk of cardiovascular death or sudden death after PCI [ 19 ]. However, the proportion of patients with AMI was 10–20% in those previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study by Aydınlı B et al [ 18 ] found no association of high HbA1c levels with immediate CABG results. The reasons for such contradictions during long-term follow-up of patients can be numerous; one of them is shown in the study by Funamizu T, et al, where strict control of diabetes achieving the HbA1c level < 6.5 in the group of diabetes patients after PCI led to a worsening prognosis during 10-year follow-up [ 28 ]. Another possible reason is the suboptimal selection of the CMD marker.…”
Section: Discussionmentioning
confidence: 99%